Management of Rotylenchulus reniformis in pineapple, Ananas comosus, by intercycle cover crops - Wang, K-H (Journal of nematology, 2002)
The effects of intercycle cover crops on Rotylenchulus reniformis population densities in pineapple were evaluated in one greenhouse and two field experiments. In the greenhouse, Crotalaria juncea, Brassica napus, and Tagetes erecta were planted for 3 months and then incorporated. These treatments were compared to weedy fallow with or without 1,3-dichloropropene (1,3-D) in three soils (Makawao fallow, Wahiawa fallow, and Wahiawa pineapple) naturally infested with R. reniformis. All cover crop incorporation suppressed R. reniformis numbers in cowpea more than did the weedy treatment in the Makawao (P < 0.05) but not in the Wahiawa soils. Crotalaria juncea treatment increased bacterivorous nematodes and nematode-trapping fungal population densities more than the other treatments in Makawao fallow and Wahiawa pineapple-planted soils. The field trials included the same plants as well as Sinapis alba. Treatments with Crotalaria juncea and 1,3-D maintained lower R. reniformis population densities on pineapple longer than other cover crops or weedy fallow treatments. Crotalaria juncea could have suppressed R. reniformis because it is a poor host and because it enhances nematode-trapping fungi when incorporated into soil. Treatment with 1,3-D reduced microbial activities but produced the greatest pineapple yield